Predictivity of right ventricular outflow tract velocity-time integral in detection of the size of secundum atrial septal defect in children - Akter, Shirin; Islam, M. Tariqul; Karim, Tahmina; Alam, M. Shakhawat; Sultana, Taslima; Aktar, Mahafuja Mortuja; Dey, Lipika (International Journal of Contemporary Pediatrics, 2025)
Background: Atrial septal defect (ASD) is a common congenital heart defect in children, with secundum ASD being the most frequent type. Unrepaired defects can cause right ventricular overload and pulmonary hypertension. While Qp:Qs ratio requires four parameters to detect shunts, the right ventricular outflow tract velocity-time integral (RVOT VTI) alone can indicate significant interatrial shunts and predict ASD size. This study aimed to evaluate RVOT VTI in predicting secundum ASD size in children. Methods: This cross-sectional study was conducted in department of pediatric cardiology, Bangladesh Medical University, Dhaka, from July 2023 to June 2024. A total of 30 patients were selected as study subjects by a purposive sampling technique. The data were coded, entered, and analyzed using Statistical Package for the Social Sciences (SPSS) version 25.0. Results: The results of this study indicate that the majority of children (60%) had an RVOT VTI >20 cm, and most secundum ASDs were moderate in size as measured by both TTE and TEE. A positive, though statistically non-significant, correlation was observed between RVOT VTI and ASD size measured by both TTE (r=0.271, p<0.147) and TEE (r=0.303, p<0.104). ROC analysis identified RVOT VTI cut-off values of 19 cm and 15 cm for differentiating large and moderate-to-large ASDs, with corresponding accuracies of 60% and 93.3%, respectively. The 15 cm cut-off demonstrated higher diagnostic performance, showing 96% sensitivity and 75% specificity. Conclusions: This study highlighted the potential role of RVOT VTI as a useful, non-invasive parameter for estimating the size of secundum ASDs in pediatric patients. It demonstrated that RVOT VTI can help distinguish between small, moderate, and large defects. At a cut-off value of 19 cm, RVOT VTI showed an accuracy of 60% in differentiating large ASDs from small to moderate ones.